The economic costs of COVID-19 in Sub-Saharan Africa: Insights from a simulation exercise for Ghana - Amewu, Sena; Asante, Seth; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2020)
The objective in this paper is to estimate the economic costs of COVID-19 policies and external shocks in a developing country context, with a focus on agri-food system impacts. Ghana is selected as a case study. Ghana recorded its first two cases of COVID-19 infection on 12 March 2020. The government responded by gradually introducing social distancing measures, travel restrictions, border closures, and eventually a partial, two-week “partial” lockdown in the country’s largest metropolitan areas of Accra and Kumasi. Social distancing measures have been enforced nationwide and include bans on conferences, workshops, and sporting and religious events, as well as the closure of bars and nightclubs. All educational institutions are also closed. The partial lockdown measures in urban areas directed all residents to remain home except for essential business, prohibited non-essential inter-city travel and transport, and only essential manufacturing and services operations were permitted to continue (The Presidency 2020). At the time the lockdown was announced, Ghana’s Ministry of Finance revised its GDP growth estimate for 2020 downwards from 6.8 to 1.5 percent (MoF 2020), although the Minister warned that growth could fall further if lockdown measures were extended. The lockdown was initially extended for a third week but was officially lifted on 20 April. Social distancing measures remain in place nationwide, although a gradual easing of restrictions commenced in June. Ghana’s borders remain closed at the time of writing.